Secret Fairy Homes - Random House; Brown(3, (BAdriennes; Holmes(3, (BJudiths (Washington Random House, 2006)
Welcome to the Home Tree! This is where Tinker Bell and all the Disney Fairies live in their own beautifully- and personally-decorated bedrooms. Girls can lift the large gatefolds on each spread of this unique and interactive book and peek inside each of the fairies' rooms. The intricate metalwork on Tink's bed, the seaweed curtains on Rani's windows, and even the saddle Beck uses when riding frogs are just a few of the delightful fairy treasures to be discovered!
12
Keywords: English stories